PERTUMBUHAN TANAMAN GAHARU (Aquilaria malaccensis lamk) ASAL PROVENANS LAIMU MORNATENG DAN PASSO PADA TANAH INSEPTISOL DI DESA HATUSUA KECAMATAN KAIRATU KABUPATEN SERAM BAGIAN BARAT - Samaung, Widya; Matinahoru, Johan; Hadijah, Miranda (PT. BARRINGTONIA ASIATICA LESTARI, 2024)
The aim of this research is to determine and analyze the ability of agarwood plants to grow on inceptisol soil and to analyze the factors that determine the growth of agarwood plants on inceptisol soil in Hatusua Village, Kairatu District, West seram Regency. The method used in this research is a completely randomized design method, the data collection technique used in this research is in the form of direct observations carried out on a demonstration plot of the source of agarwood (Aquilaria malacccensis lamk) seeds from which 3 trees were taken from each provenance. And data analysis used a completely randomized design and multiple regression analysis. The results obtained from the research were variance analysis of parameters which showed that only the leaf bones were real. The three provenances are determined by three soil factors, namely fertility, humidity and pH. Of the three soil factors, only Laimu provenance has an influence, because it has a larger F-value. And the environmental factor that has the most influence on the Laimu provenance is atmospheric humidity, while the environmental factor that has the most influence on the Mornateng provenance agarwood plant is soil moisture and the most influential environmental factor for the Passo provenance agarwood plant is light intensity.